Preparation and characterization of zein thermo-modified starch films. (10th February 2017) - Gao, Pingping; Wang, Feng; Gu, Fengying; ning, Jiying; Liang, Jun; Li, Ningbo; Ludescher, Richard D.
Highlights: Zein modified starches can be obtained by a simple dry heating method. Film functionalities from zein thermo-modified starches were obviously improved. Abstract: A new method of preparing films from zein thermo-modified starch was presented. According to data of micro-visco-amylography and rheometer, dry heating with zein significantly decreased the pasting properties of waxy corn starch and distarch phosphate, the values of G′ and G″ of starches dry heated with zein decreased, while the loss tangent increased as a function of heating time. Scanning electron microscopy images showed that the surfaces of starch granules became rough after dry heating with zein, suggesting interactions between zein and the granule surface. In films made from mixtures, the starch/zein compatibility was improved through dry heating. Compared with films cast from mixtures of separately heat-treated starch and zein, films made from the starch/zein mixtures heated together possessed higher water contact angle and tensile strength. Simple dry heating with zein could thus be used as a promising modification method for improving the functionality of edible films from starches.